The Role of the Indonesian Migrant Worker Protection Service Center (BP3MI) in Gender-Responsive Protection in Cilacap in 2024 - Fika Deliana (Badan Penerbit STIEPARI Press, 2025)
This study examines the Indonesian Migrant Worker Protection Service Center (BP3MI) of Central Java's role in providing gender-responsive protection to Indonesian Migrant Workers (PMI) from Cilacap Regency. Despite Cilacap being Central Java's largest PMI hub with 13,274 placements in 2024 (69.78% female), the persistence of 27 complaint cases ranking 9th nationally indicates significant gaps in gender-responsive protection services. This research aims to evaluate BP3MI's gender-responsive protection mechanisms and identify improvement areas for female PMI vulnerability mitigation. This qualitative study employed in-depth interviews with the Head of Protection and Empowerment Team at BP3MI Central Java, complemented by policy document analysis to assess current protection frameworks and implementation practices. Findings reveal BP3MI implements three-stage protection: pre-placement (Pre-Departure Orientation), placement (Indonesian Embassy collaboration), and post-placement (skills training). However, critical limitations emerge in gender-responsive implementation: absence of gender-differentiated OPP materials, lack of psychological counseling services, and suboptimal gender perspective integration. While early warning systems and gender-based risk profile databases exist, enhancement is required, particularly in psychosocial support and gender-based violence handling mechanisms. The study concludes that comprehensive policy strengthening and improved technical implementation are essential to optimize gender-responsive protection for PMI. Recommendations include developing gender-specific training modules, establishing dedicated psychological support services, and enhancing inter-agency coordination for better protection outcomes, particularly for female migrant workers who constitute the majority of PMI placements.